Siberians at the Festival ZODCHESTVO 2025 - Елена Григорьева (Проект Байкал)
The article provides information about the architectural festivals Zodchestvo and Best Interior Festival, as well as the BUILD SCHOOL exhibition, as well as the participants and prize winners of the events. The author observes a high level of the participants’works and the activities of Siberian branches and creative organisations. At the XVII Reporting and Electing Congress of the Union of Architects of Russia (UAR) held on 13 November 2024 in Moscow, the reports of the President of the UAR and vice-presidents for federal districts were presented, and the UAR President was elected.